Cardiorespiratory fitness in women after severe pre-eclampsia - Lasse Gronningsaeter; Mette-Elise Estensen; Helge Skulstad; Eldrid Langesaeter; Elisabeth Edvardsen (Taylor & Francis Group, 2023)
Aims To objectively study cardiorespiratory fitness (CRF) and physical activity (PA) and to evaluate limiting factors of exercise intolerance associated with poor CRF after severe pre-eclampsia. Methods In this single-centre, cross-sectional study, CRF was measured as peak oxygen uptake (VO2peak) during a cardiopulmonary exercise test (CPET) on a treadmill in women 7 years after severe pre-eclampsia. Ninety-six patients and 65 controls were eligible to participate. Cardiac output (CO) was measured by impedance cardiography. PA was measured using accelerometers. Results In 62 patients and 35 controls (mean age 40 ± 3 years), the VO2peak (in mL·kg-1·min-1) values were 31.4 ± 7.2 and 39.1 ± 5.4, respectively (p<0.01). In the patients, the COpeak was (9.6 L·min-1), 16% lower compared to controls (p<0.01). Twelve patients (19%) had a cardiac limitation to CPET. Twenty-three (37%) patients and one (3%) control were classed as unfit, with no cardiopulmonary limitations. The patients demonstrated 25% lower PA level (in counts per minute; p<0.01) and 14% more time being sedentary (p<0.01), compared with the controls. Twenty-one patients (34%) compared with four (17%) controls did not meet the World Health Organization's recommendations for PA (p=0.02). Body mass index and PA level accounted for 65% of the variability in VO2peak. Conclusion Significantly lower CRF and PA levels were found in patients on long-term follow-up after severe pre-eclampsia. CPET identified cardiovascular limitations in one third of patients. One third appeared unfit, with adiposity and lower PA levels. These findings highlight the need for clinical follow-up and exercise interventions after severe pre-eclampsia.